Second near-infrared light-activatable polymeric nanoantagonist for photothermal immunometabolic cancer therapy - Xu, Cheng (2022)
Immunometabolic modulation offers new opportunities to treat cancers as it is highly associated with cancer progression and immunosuppressive microenvironment. However, traditional regimens using nonselective small-molecule immunomodulators lead to the off-target adverse effects and insufficient therapeutic outcomes. Herein a second near-infrared (NIR-II) photothermally activatable semiconducting polymeric nanoantagonist (ASPA) for synergistic photothermal immunometabolic therapy of cancer is reported. ASPA backbone is obtained by conjugating vipadenant, an antagonist to adenosine A2A receptor, onto NIR-II light-absorbing semiconducting polymer via an azo-based thermolabile linker. Under deep-penetrating NIR-II photoirradiation, ASPA induces tumor thermal ablation and subsequently immunogenic cell death, triggers the cleavage of thermolabile linker, and releases the antagonist to block the immunosuppressive adenosinergic pathway. Such a remotely controlled immunometabolic regulation potentiates cytotoxic T cell functions while suppresses regulatory T cell activities, leading to efficient primary tumor inhibition, pulmonary metastasis prevention, and long-term immunological memory. Thereby, this work provides a generic polymeric approach for precise spatiotemporal regulation of cancer immunometabolism.